Loss of Advocate Immunity Due To Obstruction Of Justice Based On Criminal Provisions - Gayo, Sabela (Faculty of Law, Universitas Pattimura, 2022)
Introduction: The enforceability of Article 16 and the Constitutional Court decision number 26/PUU-XI/2013 does not necessarily exempt advocates from alleged intervention in the enforcement process in carrying out their profession to defend clients, but that right can be lost said the lawyer committed a criminal act of Obstruction of Justice.Purposes of the Research: The purpose of this study is to explain the right of attorney immunity can be lost when committing a criminal act of Obstruction of Justice.Methods of the Research: The research method used is normative legal research with a statute legal approach and a conceptual approach.Results of the Research: Advocates in terms of exercising their profession require immunity rights, but the use of immunity rights has definitive conditions that must be considered as stipulated in Article 16 of law no. 18 of 2003. The act of an advocate should be suspected of committing a criminal act of obstruction of justice if the act is not related to his professional duties and is not based on good faith. The action taken by The Advocate in relation to his professional duties has the meaning that the action is carried out for the benefit of the client's defense. Good faith referred to in Article 16 is to carry out professional duties for the sake of establishing justice based on the law to defend the interests of its clients.